2023
DOI: 10.1002/chem.202301517
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Reversible Oxidation of Sub‐Nanometric Cu5 Metal Clusters: Integrated Experimental Study and Theoretical Modeling**

Abstract: Sub-nanometer metal clusters have special physical and chemical properties, significantly different from those of nanoparticles. However, there is a major concern about their thermal stability and susceptibility to oxidation. In situ X-ray Absorption spectroscopy and Near Ambient Pressure X-ray Photoelectron spectroscopy results reveal that supported Cu 5 clusters are resistant to irreversible oxidation at least up to 773 K, even in the presence of 0.15 mbar of oxygen. These experimental findings can be formal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(143 reference statements)
0
3
0
1
Order By: Relevance
“…In that case, it was also found that the different copper atoms could present different oxidation states, in good agreement with the experiment. 36 However, DOS results unequivocally demonstrate that [Cu 6 ] 2+ lacks spin states. Therefore, we conducted charge difference density analysis, 37 revealing that as a copper cluster, Cu 6 has collectively lost two charges (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In that case, it was also found that the different copper atoms could present different oxidation states, in good agreement with the experiment. 36 However, DOS results unequivocally demonstrate that [Cu 6 ] 2+ lacks spin states. Therefore, we conducted charge difference density analysis, 37 revealing that as a copper cluster, Cu 6 has collectively lost two charges (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, the electronic and catalytic properties of clusters composed by a precise small number of atoms are different from those of larger nanoparticles and isolated metal cations, and can be further modulated by interactions with organic ligands or inorganic supports. 21–25 More specifically, it has been computationally predicted and experimentally confirmed that Cu 5 clusters are able to activate molecular O 2 and generate reactive O species while avoiding deep irreversible oxidation, 26–29 which makes them promising candidates for a variety of catalytic applications. 30–32 Previous computational work in our group indicates that O species bicoordinatively adsorbed at the edges of isolated Cu 5 clusters favour the homolytic dissociation of the methane C–H bond and the selective formation of methanol following a radical rebound mechanism similar to that described for Cu-exchanged zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…This variability manifests itself, for example in a competition between nearly isoenergetic three-dimensional and (quasi-)two-dimensional structures in a characteristic size range. 5,6 The resulting structural fluxionality plays a key role in rationalizing the properties of supported metal clusters, [7][8][9][10] including Ag 5 on a TiO 2 support. [11][12][13] In order to better understand and predict how a cluster's fluxionality is affected by the environment, it proves helpful to study the intrinsic properties of clusters isolated in the gas phase.…”
Section: Introductionmentioning
confidence: 99%